Measuring the tax effort of developed and developing countries. Cross country panel data analysis – 1985/95 - Marcelo Piancastelli (Institute for Applied Economic Research (ipea), 2015)
In the tax literature, the tax effort index for any country is usually measured by the ratio of the actual tax ratio to the predicted ratio. This reflects mainly the variance in the taxable capacity of a country. A high value of tax effort index indicates that a particular country is collecting more tax than would be predicted, given its tax structure and prevailing economic and social conditions. This paper estimates the tax effort index for a sample of 75 countries for the period 1985/95. It incorporates the most recently available data and also econometric techniques not used before for such a type of analysis. The results are then compared with previous studies encompassing different periods over the last 30 years. The evidence provided in this paper suggests that per capita income, the ratio of trade to GDP, and the share of agriculture in GDP of the product of the agricultural sector are the most consistent explanatory variables of the tax ratio, while several variables used in previous studies, such as the ratio of mining output to GDP, and the ratio of quasi-money to GDP, are not significant in the recent period under analysis. This paper shows those countries that have improved their tax performance, measured by the tax effort index, as well as those which have a less favourable performance. Tax ratios and tax effort comparisons are also made among the developed and developing countries according to income groups and different continents.
Keywords: H20; H21; H30; 330; tax effort; tax revenue; tax ratio